Modeling and performance analysis of a thermoelectric energy harvesting system from logger housing for water utility company applications - Valdez, Victor B.; Berana, Menandro S. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
A thermoelectric generator, (TEG) unit, utilizing the absorbed heat energy from instrument enclosures caused by direct solar radiation has the potential to minimize the consumption of disposable batteries being utilized on instrumentation components like data loggers and flow meters. A thermoelectric energy harvester could be combined with a battery and serve as a complementary source of power device due to the limited size of the main battery. This arrangement can also mitigate data unavailability and data losses once the main battery has depleted. Remote monitoring instruments like data loggers and flow meters are being used by water utility companies for flow and pressure measuring and monitoring purposes and other water supply management applications. The TEG unit is installed directly in contact inside a data logger housing or enclosure. The radiant heat energy captured by the housing will be transferred to the TEG by conduction, thus will be kept at high temperature as long as the enclosure is exposed to sun's radiance. A pressure reducing valve (PRV), which is also installed in the piping system inside the chamber, is used to circulate cold water into the TEG system. The existence of the PRV substitutes the need for a pump to supply cold water by utilizing the pressure difference between its inlet side (high pressure) which is connected to the tube that would supply the cold water to the TEG's cold side and then from the TEG cold side to the outlet side (low pressure) of the PRV for the release of the heated water coming from the TEG. This would prevent the cold side to be in thermal equilibrium with the hot side since there will be continuous flow of cold water coming from the PRV cold source set up. The main principle is to maintain the temperature difference between the hot side and cold side of the TEG in order for the semiconductor materials to continue creating the desired electrical energy. The power generation of the TE unit was validated using ANSYS software (Academic version), and the projection of the annual energy generation of the harvesting unit was computed based on the data gathered from the lab-based experiment. Findings from the lab-based experiment also showed that the optimum array configuration of TE modules was from straight-series connection with a projected energy generation of 46.61 kWh per year. The projected energy was not enough to exceed the annual energy demand of 52.80 kWh and this only confirms that power autonomy using the thermoelectric energy harvesting was not applicable for the current arrangement. It is recommended, however, that the substantial harvested energy which is 88% of the demand, should be combined with the main battery and serve as a complementary source of power to provide energy and extend the battery life of the data logger device.
Thesis (Master of Science in Mechanical Engineering)--University of the Philippines Diliman
Keywords: Thermoelectric generators; Energy harvesting